A DNA binding protein that recognizes oligo(dA).oligo(dT) tracts. - Winter, E (1989)
Oligo(dA).oligo(dT) tracts are common intergenic sequences in many organisms. In the yeast Saccharomyces cerevisiae, these sequences have been shown to influence transcription of adjacent genes. We have purified an oligo(dA).oligo(dT)-binding protein from S. cerevisiae and cloned its gene. This protein, which has been named datin, requires at least 9-11 bp of oligo(dA).oligo(dT) DNA for high affinity binding. The gene for datin (the DAT gene) encodes a 248-residue protein which contains a number of repeated sequence motifs. Datin purified from yeast corresponds to the N-terminal half of the DAT gene product. Null mutants in the DAT gene are viable but phenotypically distinguishable from congenic wild-type strains. We discuss unusual structural features and biochemical properties of datin in relation to its possible functions.